KOMUNIKASI DAN SUMBER DAYA DALAM IMPLEMENTASI PROGRAM E-WARONG KUBE PKH - Ariesta Amanda; Lupita Ariantika Sari; Thahrina Azriah (Economics, Social, and Humanities Journal (Esochum), 2022)
This research is entitled “Communication and Resources in the Implementation of the E-Warong Kube PKH Program. This research is motivated by the existence of the E-Warong KUBE-PKH program, the distribution of social assistance has shifted from being initially cash to non-cash. The purpose of this study is to describe how communication and resources are in the Implementation of the Electronic Program of the Mutual Cooperation Stalls Joint Business Group for the Family Hope Program (E-Warong Kube PKH) in Banyumas Regency. This study was used qualitative research methods. The informant selection technique used was purposive sampling technique. Methods of data collection employed were interviews, observation, and documentation. The results of the study show that the implementation of the Mutual Cooperation Warung Electronic Program for the Family Hope Program (E-Warong Kube PKH) in Banyumas Regency has been running optimally. Communication runs quite optimally and there is coordination between parties. The communication methods used are formal and informal. Informal communication via WA groups is very helpful in exchanging information, especially when it comes to disbursing aid, obstacles and handling them. The intensity of the communication carried out was quite good, it was just lacking in terms of delivering the detailed functions and benefits of the E-Warong Kube-PKH program. Human and financial resources are sufficient, but human resources in terms of competence there are still actors who come from low KPM resources or come from pre-prosperous families so that they have not been able to maximize the implementation of KUBE E-Warong development.